(untitled) (London, 1996)
Contents: Japan is now the biggest donor of Official Development Assistance (ODA) throughout the world. This study takes a new approach to this subject by focusing on the procedures, methodologies and business mechanisms at the implementation level that influence the process of policy-making in Tokyo. It is also the first study to explore the process of receiving aid, arguing that many of the recipient countries exert considerable influence over the distribution of Japanese foreign aid.
Keywords: Economic assistance,Hỗ trợ kinh tế; Japanese Asia Case studies,Nghiên cứu điển hình tại Nhật Bản